Chiral evolution of carbon dots and the tuning of laccase activity. Issue 5 (12th January 2018) - Hu, Lulu; Li, Hao; Liu, Chang'an; Song, Yuxiang; Zhang, Mengling; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Chiral CDs synthesized by an alkali-assisted method have been demonstrated to tune the activity of laccase selectively for the first time. Abstract : Chirality has attracted extensive attention in many fields ranging from chemistry to life sciences. Carbon dots (CDs) with good biocompatibility and unique photochemical properties have become a new star in the nanocarbon family. Endowed with chirality, CDs will exhibit more marvellous properties and bridge the fields of material chemistry and life sciences tightly. Herein, we report a facile one-step alkali-assisted electrochemical method to fabricate chiral CDs from cysteine (cys). We showed the chiral evolution of CDs with highly symmetrical circular dichroism (CD) signals in the range from 205 to 350 nm. These chiral CDs have been further demonstrated to be capable of tuning the activity of laccase: thel -CDs can improve the activity of the enzyme up to 20.2%, whereas thed -CDs decrease the activity to 10.4%. A series of experiments confirm that it is the synergistic effect of nanosize and chirality of CDs that induces the change in the structure of laccase and thus leads to the tuning of the laccase activity.